2022
DOI: 10.2478/cee-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Red Sand Particle Size and Composition in Mixture with Ordinary Sand to Enhance Concrete Quality

Abstract: In this study we determined the effect of variations in composition and particle size of Red Sand (RS) grains on the quality of concrete. Concrete was prepared as cubes of 15 cm3 with a composition of cement, sand and gravel in a ratio 1:2:3 and water to cement ratio of 0.5. Variations of RS (fine aggregate) composition are 0 %, 5 %, 10 %, 15 %, 20 % of the weight and red sand grain particle size were prepared as 80 mesh, 100 mesh, 120 mesh. Mechanical properties of the maximum concrete pressure strength test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the research [4,5], it is concluded that the composition of under 5 % red sand can cover the cavities in the concrete induce the water trapped in the concrete in small amount which means it can shrink the porosity of the concrete and increase the strength value of the concrete. This means that the quantity of the composition range used in concrete production affects the improvement in its compressive strength.…”
Section: (B) Compressive Strengthmentioning
confidence: 99%
“…In the research [4,5], it is concluded that the composition of under 5 % red sand can cover the cavities in the concrete induce the water trapped in the concrete in small amount which means it can shrink the porosity of the concrete and increase the strength value of the concrete. This means that the quantity of the composition range used in concrete production affects the improvement in its compressive strength.…”
Section: (B) Compressive Strengthmentioning
confidence: 99%